Improvement of Sintering Performance of Nanosilver Paste by Tin Doping. (22nd January 2020) - Yang, Hui; Wu, Jihui
Abstract : Nanosilver paste, an interconnect solder, is a common choice in the electronics packaging industry. However, higher sintering temperature and lower sintering strength limit its application. At present, doped nanosilver paste has been studied for use in chip interconnection. In order to improve the sintering properties and shear strength of nanosilver paste, we have developed a new tin-doped nanosilver paste (referred to as silver tin paste), and according to the decomposition temperature of the organic dispersant in the slurry, a corresponding sintering process with a maximum temperature of 300°C was developed. The product after sintering of the silver tin paste is a mixture of a solid solution of Ag and an Ag3 Sn phase. Among them, the hard and brittle phase Ag3 Sn diffuse distribution in the silver matrix for strengthening, and the solid solution of Ag acts as a replacement solid solution strengthening. As the content of doped Sn increases, the sintering strength increases remarkably. When the Sn content is 5%, the joint shear strength reaches the highest value of 50 MPa. When it exceeds 5%, the sintering strength gradually decreases, which may be caused by the excessive formation of the intermetallic compound IMC as the dopant content increases. This new tin-doped nanosilver technology has the characteristics of low-temperature sintering and high-temperature service, so it is expected to be widely used in semiconductor power devices.